The role of international laws and organizations aimed at protecting journalists in armed conflicts - Kabdyl Н.Н.; Sak Қ.Ө. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The intensity of armed conflicts on the international stage is increasing, posing significant risks to the lives of journalists disseminating information from conflict zones. This article provides a comprehensive analysis of the role of international laws and organizations in ensuring the protection of rights and safety of journalists in armed conflict situations. The study focuses on examining the application and effectiveness of international legal acts, including the Geneva Conventions and their Additional Protocols, as well as analyzing the activities of major international organizations such as the UN and UNESCO, the Committee to Protect Journalists, and Reporters Without Borders. The authors highlight the historical essence of the development of international humanitarian law and emphasize its adaptation to modern conditions of warfare, characterized by diversity and ambiguity in conflicts. Special attention is given to the analysis of problems and challenges faced by journalists in conflict zones, and the role of international organizations in protecting their rights and freedoms. The article also presents recommendations for strengthening international and national defense mechanisms, as well as the need to improve informational support and educational programs for journalists working in conflict zones. In the conclusion of the research, the authors underscore the importance of global collaboration for the effective protection of journalists, identifying the necessity for further development and refinement of international regulatory mechanisms in the context of the constantly changing nature of armed conflicts.